Neural and cognitive function in a pediatric brain injury model: The impact of task complexity. (October 2022) - Cox, Elizabeth; Tseng, Julie; Bells, Sonya; Dockstader, Colleen; Laughlin, Suzanne; Bouffet, Eric; de Medeiros, Cynthia; Mabbott, Donald J.
Abstract: Acquired brain injury (ABI) in childhood/adolescence results in dysfunctional neural and attentional resources during minimal and higher task load. Impact of injury on these resources during increasing load, when task design (e.g., stimuli, timing) is held constant, is not yet well understood. We examined neural communication, processing speed and controlled attention in pediatric brain tumor survivors (PBTS; M time since treatment = 6.78 years) and typically developing children (TDC; n = 57). Participants performed simple-go and choice reaction time (RxnT) tasks during magnetoencephalography. The weighted phase lag index estimated seed-based and whole-brain functional connectivity. Group differences were assessed using tmax and network based statistics. Mean RxnT and response accuracy measured performance. Linear models assessed group differences. Tasks were analyzed individually to account for a difference in trial numbers. During both tasks, PBTS demonstrated decreased seed-based connectivity in the high gamma frequency (60–100 Hz; p < .01) relative to TDC. During the choice task alone, PBTS also demonstrated decreased theta (4–7 Hz) and alpha (8–12 Hz) seed-based connectivity ( p < .01), and increased RxnT in adolescence ( p < .05). ABI in childhood/adolescence may predominantly disrupt recruitment of neural and attentional resources necessary for higher load tasks. These findings advance understanding of the impact of task load on brain function and cognition during development, and effects of injury.